2000
DOI: 10.1046/j.1365-2672.2000.01136.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic differentiation of an antifungal biocontrol strain belonging toBacillus subtilis

Abstract: Physiological and molecular fingerprints of biotechnologically relevant rhizobacteria are necessary for registration, patenting, recognition and quality checking of the strains. To characterize the biological control agent, Bacillus subtilis B2g, the strain was compared with other plant‐associated B. subtilis isolates. Phenotypic characterization included biochemical and nutritional properties, in vitro activity and analysis of potential antagonistic mechanisms towards several plant pathogenic fungi. According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 41 publications
2
44
0
Order By: Relevance
“…Jedabi and Awatif (2009) have reported similar elevation in root colonization assay for different species of Bacillus after four days of germination, when compared to the control with 100 cfu/cm root length count. Several other research groups have reported similar results on lowered disease incitation and enhanced growth through heightened root colonization (Bais et al, 2004;Basha and Ulaganathan 2002;Marten et al, 2000). Thus, the study identifies the elevated root colonisation ability of B. subtilis better than the untreated control.…”
Section: Root Colonisation Assay (In Vitro)supporting
confidence: 69%
“…Jedabi and Awatif (2009) have reported similar elevation in root colonization assay for different species of Bacillus after four days of germination, when compared to the control with 100 cfu/cm root length count. Several other research groups have reported similar results on lowered disease incitation and enhanced growth through heightened root colonization (Bais et al, 2004;Basha and Ulaganathan 2002;Marten et al, 2000). Thus, the study identifies the elevated root colonisation ability of B. subtilis better than the untreated control.…”
Section: Root Colonisation Assay (In Vitro)supporting
confidence: 69%
“…Recent studies deal with the genetic diversity of strains of B. subtilis (30,36,38,48,56), and the two closely related species B. licheniformis and B. pumilus have been placed in the B. subtilis group.…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative assay for chitinase production was performed according to the method described by Marten et al (2000). The cultures of the Bacillus spp.…”
Section: Production Of Cell Wall Degrading Enzymementioning
confidence: 99%